Boron Beyond the Icosahedral Barrier: A 16‐Vertex Metallaborane1. Issue 11 (4th February 2013) - Roy, Dipak Kumar; Bose, Shubhankar Kumar; Anju, R. S.; Mondal, Bijan; Ramkumar, V.; Ghosh, Sundargopal
<x xml:space="preserve">Abstract</x> A neutral metallaborane comprising a Rh4B12 polyhedron with icosioctahedron geometry with 16 vertices and 28 triangular faces was prepared (see structure; Rh: red, B: green). The cage has the shape of a 12‐membered truncated tetrahedron with four capped hexagonal faces.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>